Migrants Entrepreneurs in East Nusa Tenggara - Marthen L. Ndoen; Cees Gorter; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2000)
The outer islands in Indonesia are often seen as the main source of migrants to the island of Java, whileonly a few studies look the other way round. This paper attempts to address factors that play a key role inthe migrants' propensity to stay in East Nusa Tenggara. There are six socio-economic factors used in thisstudy. It appears that access to the market in the current region is the most important variable to keep themigrants in this region.
Keywords: 330; Entrepreneurship-Ansatz; Kleine Sundainseln; Migranten